The Governance of Top-Level Domain (TLD) to Support Advancement of Internet Promotion and Innovation in Indonesia - Akbar, Maulana; Agustinah, Aminah; Syafuddin, Khairul; Andrias, Khemal; Hardiansyah, Fikri Andhika; Kuntarto, Hario Bismo; Cendana, Cendana (STI Policy and Management Journal, 2024)
The internet is a widely accessible public resource that serves as a primary driver of the digital economy. across the realm of internet governance, Top Level Domains (TLDs) assume a significant function in facilitating the expansion of internet accessibility, hence enhancing its utilisation and dissemination across society. This study examines the global patterns in top-level domain (TLD) management, identifies common challenges in TLD management within Indonesia, and assesses the appropriateness of management strategies for Indonesia, particularly in relation to internet promotion as a means of contributing to economic growth and societal advancement. Additionally, it explores the potential for fostering innovation within the country's TLD management practises. The digital economy refers to the economic activities and transactions that are conducted through digital technologies and platforms. This study examines the government's role as a regulator in shaping this trajectory. However, it is important to exercise caution to ensure that the TLD business process operates autonomously, minimising undue political interference.